ANALISIS NOVEL SITI NURBAYA KARYA MARAH RUSLI - Erlina Erlina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This research aims to analyze the intrinsic elements that constitute the novel Siti Nurbaya by Marah Rusli. This novel is a phenomenal classic Indonesian literary work that addresses crucial issues regarding the clash between love and traditional Minangkabau customs. The research method employed is descriptive qualitative with a structural literary approach. The analysis results indicate that the main theme, which is a tragedy of love hindered by customs, characterization that represents the conflict between modernity and traditionalism, and a systematic progressive plot, serve as the foundation for building the novel's narrative. This research concludes that Siti Nurbaya is not merely a romance story but a strong social critique of the rigidity of customs at that time.Keywords: Siti Nurbaya, Marah Rusli, Intrinsic Elements, Custom Critique, Classic Literature